STUDENTS’ PERCEPTIONS: ENHANCING VOCABULARY MASTERY THROUGH VOCABULARY CARDS BANK PROJECT ON INSTAGRAM - Nurlaily Nurlaily (IKIP Siliwangi, 2021)
This study investigated how students are stimulated to improve their vocabulary through the Vocabulary Card Bank project on Instagram and how they perceive it. The students were instructed to create their vocabulary cards weekly for one semester on Instagram. In this mixed-method study, the participants were first-year students in English Language Education Department at Universitas Internasional Batam. All data were collected using a questionnaire and interview. The findings showed that the majority of the students who participated in this study recognize the Vocabulary Cards Bank Project has many benefits as it can improve their vocabulary and write sentences in English. The vocabulary card posted on Instagram helped them find new English words other than textbooks and dictionaries. The results of this study are expected to motivate prospective English teachers and future researchers to apply other methods in teaching English. Keywords: Vocabulary Cards Bank, Teaching Vocabulary, English Teaching, Instagram